Risk, determinants, and persistence of long-COVID in a population-based cohort study in Catalonia - Manolis Kogevinas; Marianna Karachaliou; Ana Espinosa; Susana Iraola-Guzmán; Gemma Castaño-Vinyals; Laura Delgado-Ortiz; Xavier Farré; Natàlia Blay; Neil Pearce; Magda Bosch de Basea; Eva Alonso Nogués; Carlota Dobaño; et al. (BMC Medicine)
Abstract Background Long-COVID has mostly been investigated in clinical settings. We aimed to assess the risk, subtypes, persistence, and determinants of long-COVID in a prospective population-based study of adults with a history of SARS-CoV-2 infection in Catalonia. Methods We examined 2764 infected individuals from a population-based cohort (COVICAT) established before the pandemic and followed up three times across the pandemic (2020, 2021, 2023). We assessed immunoglobulin (Ig)G levels against SARS-CoV-2, clinical, vaccination, sociodemographic, and lifestyle factors. Long-COVID risk and subtypes were defined based on participant-reported symptoms and electronic health records. We identified a total of 647 long-COVID cases and compared them with 2117 infected individuals without the condition. Results Between 2021 and 2023, 23% of infected subjects developed long-COVID symptoms. In 56% of long-COVID cases in 2021, symptoms persisted for 2 years. Long-COVID presented clinically in three subtypes, mild neuromuscular, mild respiratory, and severe multi-organ. The latter was associated with persistent long-COVID. Risk was higher among females, participants under 50 years, of low socioeconomic status, severe COVID-19 infection, elevated pre-vaccination IgG levels, obesity, and prior chronic disease, particularly asthma/chronic obstructive pulmonary disease and mental health conditions. A lower risk was associated to pre-infection vaccination, infection after omicron became the dominant variant, higher physical activity levels, and sleeping 6–8 h. Vaccination during the 3 months post-infection was also protective against long-COVID. Conclusions Long-COVID persisted for up to 2 years in half of the cases, and risk was influenced by multiple factors.